2017
DOI: 10.17126/joralres.2017.026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HPV and EBV infection and their relationship with the p53 and PCNA expression in oral carcinoma patients.

Abstract: Introduction: Infection caused by potentially oncogenic viruses, such as HPV and EBV, favors the role of certain oncoproteins that can induce dysplasias and malignant lesions. Objective: To evaluate the prevalence of HPV and EBV and their relation with the expression of p53 and PCNA in patients with oral carcinoma. Methodology: Twenty-seven oral squamous cell carcinomas (OSCC) were evaluated; DNA extraction was conducted using the QIAamp DNA mini kit; viral detection was obtained using the IN-NO-LiPA kit for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
4
2
0
3
Order By: Relevance
“…On the other hand, we found that 45.3% of oral cancer cases are positive for high-risk HPVs, similar to previous studies [60]. The most frequent high-risk HPV types in Bosnian SCC patients are (HPVs-16, -18, -45 and -58) (21.4%, 56.1%, 27.5% and 47.9%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, we found that 45.3% of oral cancer cases are positive for high-risk HPVs, similar to previous studies [60]. The most frequent high-risk HPV types in Bosnian SCC patients are (HPVs-16, -18, -45 and -58) (21.4%, 56.1%, 27.5% and 47.9%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this investigation, the average age was maintained within the range described of 60.34 ± 14.48 years (range 19-89), and in agreement with the previous reports, this type of malignity presents most frequently between the fifth and seventh decades of life, with a mean average of 62 ± 12 years [12]. Sixty-six percent of the samples evaluated were positive for the presence of the HPV genome, this value is higher than that reported by the other works which report the viral detection averages of 39%-40% [13,14], 60% according to Yang et al (2019) [15] and even 61% according to Koskinen et al [9]; however, it remains within the averages reported by the other authors [16,17]. Regarding genotype, HPV-16 was the most frequent in single infection form (17%), noting that the infection in this genotype be it in the form of co-infection or mixed infection was present in a considerable number of the analysed cases.…”
Section: Discussionsupporting
confidence: 53%
“…HPV detection was performed using the INNO-LiPA HPV Genotyping Extra Kit (Innogenetics), following the commercial specifications. The kit allows specific detection of 25 HPV genotypes (HPV types 6,11,16,18,31,33,35,39,40,42,43,44,45,51,52,53,54,56,58,59,66,68,70,73,74), and it is based on reverse hybridisation. The test included a PCR amplification of a 65 bp fragment within the L1 region of the HPV genome using the broad-spectrum SPF10 biotinylated primers.…”
Section: Detection and Genotyping Of The Human Papillomavirusmentioning
confidence: 99%
“…Entretanto, barreiras sociais ainda precisam ser ultrapassadas para que esses profissionais consigam intervir de maneira eficaz em fatores determinantes para o processo de saúde-doença de seus pacientes [33][34][35] . Tais barreiras incluem, principalmente, a dificuldade da abordagem de assuntos relacionados a doenças sexualmente transmissíveis, como o HPV [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: A Importância Da Atuação Do Cirurgião-dentistaunclassified
“…Ressalta-se, ainda, que o exame clínico e o adequado acompanhamento permitem que ocorra a detecção de diversas lesões, anomalias e alterações na cavidade bucal [22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Ademais, a identificação precoce de lesões potencialmente malignas, como o carcinoma epidermoide bucal, permite que as chances de cura aumentem consideravelmente 33 .…”
Section: A Importância Da Atuação Do Cirurgião-dentistaunclassified